Kegiatan Unit Kesehatan Sekolah Dengan Perilaku Hidup Bersih Dan Sehat Tatanan Sekolah Di SMA Negeri 1 Manganitu Kabupaten Kepulauan Sangihe - Dismo Katiandagho; Steven J Soenjono (Jurnal Kesehatan Lingkungan, 2021)
Adolescent forms of deviation as a result of development such as smoking behavior, alcoholic beverages, drug use, stress and trauma. The purpose of this study was to determine the relationship between the activities of the school health unit (UKS) with clean and healthy living behavior (PHBS) in SMA Negeri 1 Manganitu. The type of this research is analytic observational with a cross sectional study design, the sample size in this study is 62 students.. Data collection will be done directly by conducting interviews. The research data were analyzed univariate and bivariate by using the test Chi square. The results showed that there was a significant relationship between using healthy latrines and PHBS, value p = 0.001; PR = 8,775, there is a significant relationship between smoking behavior at school and PHBS, p = 0.026; PR = 20.148, there is a significant relationship between eradicating mosquito larvae with PHBS value p = 0.026; PR = 20.148, and there is a significant relationship between waste disposal and PHBS,value p = 0.014; PR = 46,667. The conclusion of this study is that there is a significant relationship between using healthy latrines, non-smoking behavior in schools, eradicating mosquito larvae and disposing of garbage in its place with clean and healthy living behavior. It is recommended for the school to educate students and teachers through counseling and installation of leaflets prohibiting smoking in schools and providing cleaning water for latrines. For the puskesmas to provide assistance for UKS so that it continues to run well and support every UKS program implemented in schools.